SISTEM KEBIJAKAN OBJEK VITAL, PENGAMANAN FILE, DAN PENGAMANAN CYBER PT. BANK NEGARA INDONESIA (Persero) Tbk. - Edy Soesanto; Arya Bayu Sayeti; Nikken Syakira Haq; Rewang Budi Prasetyo (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
To prevent unsettling influences and errors that can derail repair cycles, a viable and effective security framework is needed. Through the Presidential Decree of the Republic of Indonesia No. Pamobvitnas (National Vital Objects Security) of 2004 regulates how the National Police, the Government, and related stakeholders work together to strive to create national security stability and specifically organize security for vital object countries. This study used qualitative research. The research design used in this study is qualitative descriptive. Data obtained from research conducted at Bank Negara Indonesia branch offices. In addition to direct research into the field, data acquisition is also from various sources on the internet. The research location in this study is the Bank Negara Indonesia Branch Office which is located at Jl. Pramuka, Pengasinan, Kec. Rawalumbu, Kota Bekasi, West Java 17114. A circular instructing all branches to increase vigilance was issued in response to efforts to find out the situation and conditions before the robbery occurred. The general nature of the instructions in the Circular and the fact that they do not provide technical instructions on how to raise awareness and what actions should be taken to improve security pose obstacles in their implementation. Security management is designed to prevent unwanted things from happening in the company that cause a sense of insecurity and comfort in the company. Bank Negara Indonesia, which is engaged in Indonesian banking institutions, in addition to creating a safe and comfortable corporate environment for employees, must also maintain customer data properly so that it is not leaked and misused by irresponsible parties.